Suppression of pleiotropic effects of functional cryptochrome genes by Terminal Flower 1 - Buchovsky, Ana Sabrina (2008)
TERMINAL FLOWER 1 (TFL1) encodes a protein with similarity to animal phosphatidylethanolamine-binding proteins and is required for normal trafficking to the protein storage vacuole. In Arabidopsis thaliana the tfl1 mutation produces severe developmental abnormalities. Here we show that most aspects of the tfl1 phenotype are lost in the cry1 cry2 double-mutant background lacking cryptochromes 1 and 2. The inhibition of hypocotyl growth by light is reduced in the tfl1 mutant but this effect is absent in the cry1 or cry2 mutant background. Although the promotion of flowering under long rather than short days is a key function of cryptochromes, in the tfl1 background, cryptochromes promoted flowering under short days. Thus, normal CRY control of photoperiod-dependent flowering and hypocotyl growth inhibition requires a functional TFL1 gene